Prevalence of Vibrio parahaemolyticus, Vibrio cholerae, and Vibrio alginolyticus in a white-leg shrimp (Litopenaeus vannamei) farm in Sarawak - Robin, Tunung; Nillian, Elexson; Lesen, Dalene; Awang Baki, Dayang Najwa (Universiti Putra Malaysia Press, 2024)
Vibriosis in shrimp farms poses potential risks to the industry’s sustainability and the consumers’ health. Little is known about the dynamics and variation of Vibrio spp—population in shrimp production in Sarawak, Malaysia. The apparent prevalence of three Vibrio species, V. parahaemolyticus, V. cholerae, and V. alginolyticus, were investigated in water (n=12), sediment (n=12), shrimp (n=12), and effluent (n=12) samples collected from two ponds in a coastal shrimp farm during one production cycle. Multiplex-PCR using specific primer sets showed the presence of the three Vibrio species. Based on the results, V. parahaemolyticus was the most prevalent in all four samples, with a contamination rate of 97.92% (95% CI: 89. 10 to 99.89%), while V. cholerae and V. alginolyticus had a contamination rate of 47.92% (95% CI: 34.37 to 61.67%) and 25.0% (95% CI: 14.92 to 38.78%), respectively. High Vibrio load in the shrimp farm is due to favourable environmental factors, such as optimal temperatures, salinity, and pH ranges for the growth of these species. The study’s findings offer important preliminary insights into the prevalence and distribution of these pathogenic Vibrio spp., within a shrimp farm in Kuching, Sarawak. This study serves as a potential model for monitoring Vibrio spp. prevalence in other shrimp farms across Sarawak, thereby addressing the scarcity of data on prevalence in the region.